Diversity-Oriented Synthesis and Chemical Genetics of Peptidomimetics to Address Lead Discovery of Anti-Infective Agents - Elena Lenci; Irene Stefanini; Antonio Guarna; Gloria Menchi; Duccio Cavalieri; Andrea Trabocchi (Proceedings, 2017)
Modern advances in Chemical Biology include the improvement of screening methods, the introduction of bioinformatic methods to unravel biological pathways, and the generation of highquality chemical libraries. [...]